2021
DOI: 10.1111/jcal.12525
|View full text |Cite
|
Sign up to set email alerts
|

Video‐enhanced or textual rubrics: Does the Viewbrics' formative assessment methodology support the mastery of complex (21st century) skills?

Abstract: Learners in the process of developing complex skills need a rich mental model of what such skills entail. Textual analytics rubrics (TR) are a widely used instrument to support formative assessment of complex skills, supporting feedback, reflection, and thus mental model development of complex skills. However, the textual nature of a rubric limits the possibility to deliver contextual and dynamic (time‐and behaviour‐oriented) information. In the Viewbrics online tool, we developed a version supporting the deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The concept of formative assessment emphasizes the integration of instruction and evaluation. It requires a dynamic, continuous framework for evaluating performance that promotes students' progress and the mastery of increasingly sophisticated skills, which is important for the cultivating of complex 21CS (Ackermans et al, 2021;Care et al, 2019;Nadolski et al, 2021). However, since complex 21CS involve complex learning of different but interconnected knowledge and competencies, formative evaluation practices in the school curricula are relatively scarce (Ackermans et al, 2021;Webb et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of formative assessment emphasizes the integration of instruction and evaluation. It requires a dynamic, continuous framework for evaluating performance that promotes students' progress and the mastery of increasingly sophisticated skills, which is important for the cultivating of complex 21CS (Ackermans et al, 2021;Care et al, 2019;Nadolski et al, 2021). However, since complex 21CS involve complex learning of different but interconnected knowledge and competencies, formative evaluation practices in the school curricula are relatively scarce (Ackermans et al, 2021;Webb et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It requires a dynamic, continuous framework for evaluating performance that promotes students' progress and the mastery of increasingly sophisticated skills, which is important for the cultivating of complex 21CS (Ackermans et al, 2021;Care et al, 2019;Nadolski et al, 2021). However, since complex 21CS involve complex learning of different but interconnected knowledge and competencies, formative evaluation practices in the school curricula are relatively scarce (Ackermans et al, 2021;Webb et al, 2018). As a result, there are still some key issues that must be explored in how to evaluate and monitor students' learning progress under complex context, such as how and when formative assessment should be offered (Bhagat and Spector, 2017;Kim, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Students are supported to form a mental model of what skills mastery level is expected of them through the availability of video-enhanced analytic rubrics and video-modeling examples, by using the rubrics on a standard video-modeling example and by comparing their feedback with the feedback of an expert. A video-enhanced rubric is an integration of a videomodeling example with example situations and role models, and an analytic rubric (Ackermans et al, 2021a(Ackermans et al, , 2021b. A video-modeling example is an (good or bad) example of task execution and associated behavior that can support observational learning and mental model formation to acquire skills.…”
Section: Unraveling the Pe(e)rfectly Skilled Method: Online Student P...mentioning
confidence: 99%
“…Studies have shown that educational technology can be used very well for the process of formative assessment. Throughout the formative assessment, teachers can use educational technology to provide evidence regarding the achievement of learning outcomes and to provide feedback and improve the teaching process [38], [39], [40]. The use of technology for assessment has had a particularly great impact on students with special needs [41].…”
Section: Topic 3 Educational Technology and Assessment Of Studentsmentioning
confidence: 99%